Nikki Tesla and the ferret-proof death ray - Keating, Jess (Keating, Jess. Elements of genius, 2019)
Nikki Tesla is a genius, so mostly she finds school boring, and amuses herself by inventing things, like her mysterious missing father; trouble is most of her inventions have serious, lethal potential (like the death ray, which just blew a hole in her floor); so she and her ferret are hustled off to the special Genius Academy with classmates who are equally exceptional, although she still worries about fitting in--but when her death ray disappears she has something bigger to worry about: who took it and what are they planning to do?